RARE SIDE EFFECT OF TOPIRAMATE - A CASE REPORT - Gopalsamy, G Srinivasagopalan; Mohan, Murali; Sankar, Sudhakar (International Journal of Clinical and Biomedical Research, 2015)
Topiramate (sulfamate-substituted monosaccharide) is a broad spectrum newer anti-convulsant. It is also used in prophylaxis of migraine, cluster headache, bipolar affective disorder, post traumatic stress disorder, post herpetic neuralgia, relapse prevention in alcohol dependence syndrome, add on treatment for antipsychotic induced weight gain. Acute Myopia and angle closure glaucoma are some of the rare side effects of topiramate. This case highlights the development of myopia in a middle aged patient with alcohol dependence syndrome while he was on topiramate therapy. KEYWORDS: Topiramate; Alcohol dependence syndrome; Angle closure glaucoma; Myopia.